Recreational, cultural and aesthetic services from estuarine and coastal ecosystems - Andrea Ghermandi; Paulo A. L. D. Nunes; Rosimeiry Portela; Nalini Rao; Sonja S. Teelucksingh (Fondazione Eni Enrico Mattei (FEEM), 2009)
The role of economic analysis in guiding the sustainable development of estuarine and coastal ecosystems is investigated based on a comprehensive review of the literature on the valuation of the recreation, cultural and aesthetic services. The implications of the findings for the sustainable management of coral reefs, Marine Protected Areas, and Small Island Developing States are discussed. Finally, the potential of meta-analytical benefit transfer and scaling up of values at various aggregation levels is demonstrated in the context of coastal tourism and recreation in Europe. The results of the study support the conclusion that the non-material values provided by coastal and estuarine ecosystems in terms of recreational, cultural and aesthetic services represent a substantial component of human well-being.
Keywords: Q20; Q26; Q57; 330; aesthetic values; coastal recreation; coral reefs; cultural values; ecosystem services valuation; ecosystem services; estuarine ecosystems; marine protected areas; non-market valuation; non-use values; passive values; recreational fishing; small island developing states; spiritual and religious values